Factors influencing demand for international tourism in Malaysia by Singaporean tourists - Chong, Boon Chiew (UNIMAS, 2009)
After the recent economic crises, Malaysia tourism has become a major export industry. Tourists from Singapore represent more than 50 percent of international tourist arrivals to Malaysia from year 1998 to 2007 (Tourism Malaysia, 2008). Therefore, it is essential to consider the factors influencing international tourism demand for Malaysia by Singaporeans. The study sets out to investigate the causal relationships between the number of Singaporean arrivals with income, transportation cost, exchange rate, consumer price index and seasonality celebration using quarterly data from period of 1998 to 2006. The results show that exchange rate, transportation cost, consumer price index and Chinese New Year season are statistically significant. The influences are theoretically consistent. The additional purpose of the study is to estimate the elasticities for income, relative price, and price of inbound tourism from Singapore to Malaysia. The results show that tourism in Malaysia is price elastic, tourism products and services in Malaysia are considered as a substitute to tourism products in other countries in the ASEAN region, and it is a luxury good to the Singaporeans.